2022
DOI: 10.1101/2022.12.05.519091
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tolerance-conferring defensive symbionts and the evolution of parasite virulence

Abstract: Defensive symbionts in the host microbiome can confer protection from infection or reduce the harms of being infected by a parasite. Defensive symbionts are therefore promising agents of biocontrol that could be used to control or ameliorate the impact of infectious diseases. Previous theory has shown how symbionts can evolve along the parasitism-mutualism continuum to confer greater or lesser protection to their hosts, and in turn how hosts may coevolve with their symbionts to potentially form a mutualistic r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…In fact, it can cause the parasite to also branch, which does not occur when the parasite evolves in isolation. This aligns with the findings of a recent theoretical study exploring the coevolution of parasite virulence and host mortality tolerance through a defensive symbiont [65]. They discovered that the defensive symbiont can cause the parasite to split into two subpopulations, resulting in the coexistence of strains with low and high virulence.…”
Section: Discussionsupporting
confidence: 88%
“…In fact, it can cause the parasite to also branch, which does not occur when the parasite evolves in isolation. This aligns with the findings of a recent theoretical study exploring the coevolution of parasite virulence and host mortality tolerance through a defensive symbiont [65]. They discovered that the defensive symbiont can cause the parasite to split into two subpopulations, resulting in the coexistence of strains with low and high virulence.…”
Section: Discussionsupporting
confidence: 88%
“…Although models of hyperparasitism are relatively rare, especially in an evolutionary context, some of our key findings are mirrored in models of other tripartite systems. For example, multiple studies have found that introducing an additional species to a host-parasite system can lead to evolutionary branching in the host (Best 2018) or the parasite (Kisdi, Geritz, and Boldin 2013; Best 2018; Smith and Ashby 2022; Morozov and Best 2012) populations. In a related study that also has relevance to biocontrol, Smith and Ashby (2022) explore how the introduction of a tolerance-conferring defensive symbiont affects the evolution of parasite virulence.…”
Section: Discussionmentioning
confidence: 99%
“…For example, multiple studies have found that introducing an additional species to a host-parasite system can lead to evolutionary branching in the host (Best 2018) or the parasite (Kisdi, Geritz, and Boldin 2013; Best 2018; Smith and Ashby 2022; Morozov and Best 2012) populations. In a related study that also has relevance to biocontrol, Smith and Ashby (2022) explore how the introduction of a tolerance-conferring defensive symbiont affects the evolution of parasite virulence. They show that even if the defensive symbiont is initially beneficial to the host population, in the long-term it is costly because it always selects for higher parasite virulence.…”
Section: Discussionmentioning
confidence: 99%
“…These pathogens had the highest virulence in naïve immunocompetent hosts relative to other evolved pathogens, but lower virulence in naïve immune-compromised hosts. Collectively, our phenotypic findings demonstrate that the immediate benefits of increased survival and pathogen tolerance conferred by the microbiota can ultimately lead to extremely negative impacts on the host 25 .…”
Section: Resultsmentioning
confidence: 88%